GPR68, a proton‐sensing GPCR, mediates interaction of cancer‐associated fibroblasts and cancer cells. Issue 3 (3rd January 2018) - Wiley, Shu Z.; Sriram, Krishna; Liang, Wenjing; Chang, Sarah E.; French, Randall; McCann, Thalia; Sicklick, Jason; Nishihara, Hiroshi; Lowy, Andrew M.; Insel, Paul A.
Abstract : The microenvironment of pancreatic ductal adenocarcinoma (PDAC) is characterized by a dense fibrotic stroma (desmoplasia) generated by pancreatic cancer‐associated fibroblasts (CAFs) derived from pancreatic stellate cells (PSCs) and pancreatic fibroblasts (PFs). Using an unbiased GPCRomic array approach, we identified 82 G‐protein‐coupled receptors (GPCRs) commonly expressed by CAFs derived from 5 primary PDAC tumors. Compared with PSCs and PFs, CAFs have increased expression of GPR68 (a proton‐sensing GPCR), with the results confirmed by immunoblotting, The Cancer Genome Atlas data, and immunohistochemistry of PDAC tumors. Coculture of PSCs with PDAC cells, or incubation with TNF‐α, induced GPR68 expression. GPR68 activation (by decreasing the extracellular pH) enhanced IL‐6 expression via a cAMP/PKA/cAMP response element binding protein signaling pathway. Knockdown of GPR68 by short interfering RNA diminished low pH‐induced production of IL‐6 and enhancement of PDAC cell proliferation by CAF conditioned media. CAFs from other gastrointestinal cancers also express GPR68. PDAC cells thus induce expression by CAFs of GPR68, which senses the acidic microenvironment, thereby increasing production of fibrotic markers and IL‐6 and promoting PDAC cell proliferation. CAF‐expressed GPR68 is a mediator of low‐pH‐promoted regulation of the tumor microenvironments, in particular to PDAC cell‐CAF interaction and may be a novel therapeutic target for pancreatic and perhaps other types of cancers.—Wiley, S. Z., Sriram, K., Liang, W., Chang, S. E., French, R., McCann, T., Sicklick, J., Nishihara, H., Lowy, A. M., Insel, P. A. GPR68, a proton‐sensing GPCR, mediates interaction of cancer‐associated fibroblasts and cancer cells. FASEB J. 32, 1170‐1183 (2018). www.fasebj.org